Splenoportographic Findings of Hepatocellular Carcinoma - TOYONAGA, Atsushi; KAJI, Hisaaki; YASUMOTO, Masatake; SAKAMOTO, Kazuyoshi; NAGASAKI, Yoshikazu; SATOMI, Takahiko; SASAKI, Ei; KURATOMI, Shintaro; FUJIMI, Tadashi; FUKUDA, Kazuo; TANIKAWA, Kyuichi (Kanzo, 1978)
Splenoportography was carried out in 121 patients in the past decade in our department and affiliated hospitals. Portograms of 13 subjects that were confirmed to have the primary hepatocellular carcinoma were retrospectively studied for the changes of portal veins. Portograms of 13 cases with hepatoma were able to be divided into four types, (1) Thrombus formation, (2) Displacement, (3) Mixture of (1) and (2), and (4) No changes. Of 13 cases, portal vein thrombi were demonstrated in 6 cases (46 per cent), and a lot of informations about the obliterative extent and status of collaterals caused by these thrombi were obtained. There were 4 cases which showed no changes (31 per cent). A diagnosis of hepatoma could not be made by means of splenoportography. In portograms, no portal branches in the space occupying lesions were demonstrated, and there was no changes in the portal vein shape which could suggest the infiltrative invasion of carcinoma.